Introduction to cryptography with coding theory. - Trappe, Wade, ....-; Washington, Lawrence Clinton, 1951- (New Jersey : Prentice Hall, 2002)
Samenvatting:For advanced undergraduate courses in cryptography and network securityin departments of math and computer science.Assumes a minimal background in programming and a level of mathsophistication equivalent to a course in linear algebra.
Keywords: Beveiliging; Cryptografie